Reengineering the business - Green, Jeremy Swinfen; Talwar, Rohit (London : BBC Enterprises, 1994)
The videos explains the fundamental elements of an important and increasingly popular management tool which allows organizations to make dramatic improvements in service, quality and efficiency through rethinking and redesigning critical business process
vol.1. Introducing reengineering - vol.2. Making reengineering work - vol.3. Reengineering in action
Keywords: Total quality management; Organizational change; Reengineering (Management); Industrial management